Proteorhodopsins dominate the expression of phototrophic mechanisms in seasonal and dynamic marine picoplankton communities - Ella T. Sieradzki; Jed A. Fuhrman; Sara Rivero-Calle; Laura Gómez-Consarnau (PeerJ, 2018)
The most abundant and ubiquitous microbes in the surface ocean use light as an energy source, capturing it via complex chlorophyll-based photosystems or simple retinal-based rhodopsins. Studies in various ocean regimes compared the abundance of these mechanisms, but few investigated their expression. Here we present the first full seasonal study of abundance and expression of light-harvesting mechanisms (proteorhodopsin, PR; aerobic anoxygenic photosynthesis, AAnP; and oxygenic photosynthesis, PSI) from deep-sequenced metagenomes and metatranscriptomes of marine picoplankton (<1 µm) at three coastal stations of the San Pedro Channel in the Pacific Ocean. We show that, regardless of season or sampling location, the most common phototrophic mechanism in metagenomes of this dynamic region was PR (present in 65–104% of the genomes as estimated by single-copy recA), followed by PSI (5–104%) and AAnP (5–32%). Furthermore, the normalized expression (RNA to DNA ratio) of PR genes was higher than that of oxygenic photosynthesis (average ± standard deviation 26.2 ± 8.4 vs. 11 ± 9.7), and the expression of the AAnP marker gene was significantly lower than both mechanisms (0.013 ± 0.02). We demonstrate that PR expression was dominated by the SAR11-cluster year-round, followed by other Alphaproteobacteria, unknown-environmental clusters and Gammaproteobacteria. This highly dynamic system further allowed us to identify a trend for PR spectral tuning, in which blue-absorbing PR genes dominate in areas with low chlorophyll-a concentrations (<0.25 µgL−1). This suggests that PR phototrophy is not an accessory function but instead a central mechanism that can regulate photoheterotrophic population dynamics.